Introduction to the Representation Theory of Algebras - Barot, Michael (Springer, 2015)
The aim of these notes is to give a brief and elementary introduction to the representation theory of finite-dimensional algebras. The notes originated from an undergraduate course I gave in two occasions at Universidad Nacional Autonóma de México. The plan of the course was to try to cope with two competing demands: to expect as little as possible and to reach as much as possible: to expect only linear algebra as background and yet to make way to substantial and central ideas and results during its progress....